1996
DOI: 10.1093/oxfordjournals.humrep.a019421
|View full text |Cite
|
Sign up to set email alerts
|

Ovary and ovulation: DNA fragmentation of oocytes in aged mice

Abstract: To investigate whether female fertility decreases with age due to poor oocyte quality, we examined the presence of DNA fragmentation in ovulated oocytes from young, mature and aged mice. Oocytes from three age groups of female mice (7-8, 20-24 and 40-48 weeks) were retrieved from the oviducts 15 h after human chorionic gonadotrophin (HCG) injection. Oocytes from each mouse were incubated in a CO2 incubator for 0-60 h in human tubal fluid (HTF). After incubation, each oocyte was stained with the terminal deoxyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
116
1
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(129 citation statements)
references
References 9 publications
8
116
1
4
Order By: Relevance
“…young mice, older counterparts show poor response to superovulation [5][6][7], increased aneuploidy rates [6][7][8] and increased FSH levels [9]. Recent data also demonstrated that oocytes from aged females contained higher levels of DNA damage [10]. These oocytes show decreased fertilization rates [11] due to delayed pronuclear formation [7] and abnormal calcium oscillations [12].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…young mice, older counterparts show poor response to superovulation [5][6][7], increased aneuploidy rates [6][7][8] and increased FSH levels [9]. Recent data also demonstrated that oocytes from aged females contained higher levels of DNA damage [10]. These oocytes show decreased fertilization rates [11] due to delayed pronuclear formation [7] and abnormal calcium oscillations [12].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…It is now clear that this spontaneous decay process in vivo as well as in vitro involves cellular fragmentation and ultimately death. [1][2][3] Cytoplasmic fragmentation has also been observed in oocytes and embryos after several in vitro paradigms. 4,5 Despite the fact that spontaneous fragmentation of the unfertilized oocyte has been documented almost three decades ago, very little is known about the cellular and molecular mechanisms governing this process.…”
Section: Introductionmentioning
confidence: 99%
“…The oocytes, like spermatozoa, may contain fragmented or damaged DNA independent of the number of chromosomes, as has been demonstrated in the rat (5). The aim of our study was to demonstrate the presence of damaged DNA in unfertilized oocytes after ICSI treatment, considering that apoptotic events in these cells could occur before treatment and thus lead to fertilization failure.…”
mentioning
confidence: 76%
“…Moreover, DNA fragmentation in oocytes associated with apoptotic evidence might be one of the reasons for poor oocyte quality and lower fertility in aged mice (5). Of greater concern would be discerning whether early apoptotic events are present in human oocytes treated with advanced techniques of assisted reproduction, in particular with intracytoplasmic sperm injection (ICSI), in which a single sperm is injected into an oocyte.…”
mentioning
confidence: 99%